The effect of gentiopicroside on brain tissue repair in mice during the acute phase of middle cerebral artery occlusion - Ling Kui; Guoyun Wang; Li Zhang; Qifeng Liao; Xi Li; Shuangshuang Wang; Tao Chen; Bingfeng Leng; Jinqun Huang; Yinming Jiao; Qiaoyuan Ye; Qingqian Zeng; et al. (Molecular Biology Reports, 2026)

Effects of clay and sand contents on phase transition and rheological shift behaviors in debris flows - Xionghuan Tan; Ni An; Tianxing Ma; Bingfeng Ye; Renjie Tang; Hongyue Sun (Engineering Geology, 2026)

Response of Earth surface hazards to underground coal mining revealed by multitemporal UAV photogrammetry - Dongdong Yang; Haijun Qiu; Zijing Liu; Zhuoyang Li; Mohib Ullah; Bingfeng Ye; Guoqing Yang (Bulletin of Engineering Geology and the Environment, 2025)

A new CNN-GRU deep learning framework optimized by CHIO for precise prediction of debris flow velocity - Liangxu Shen; Tianxing Ma; Hao Chen; Bingfeng Ye; Rui Luo; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Do post-failure landslides become stable? - Haijun Qiu; Yijun Li; Yaru Zhu; Bingfeng Ye; Dongdong Yang; Ya Liu; Yingdong Wei (CATENA, 2025)

Prominent creep characteristics of thermokarst landslides on central Tibetan Plateau under climate warming conditions - Ya Liu; Haijun Qiu; Jiading Wang; Ninglian Wang; Xingyuan Jiang; Bingzhe Tang; Dongdong Yang; Bingfeng Ye; Ulrich Kamp (CATENA, 2024)

Integrating Anthropogenic–Pesticide Interactions Into a Soil Health‐Microbial Index for Sustainable Agriculture at Global Scale - Nuohan Xu; Bingfeng Chen; Yan Wang; Chaotang Lei; Zhenyan Zhang; Yangqing Ye; Mingkang Jin; Qi Zhang; Tao Lu; Huaping Dong; Jianxin Shou; Josep Penuelas; et al. (Global Change Biology, 2024)
Soil microbiota in intensive agriculture are threatened by pesticides, economic activities, and land‐use changes. However, the interactions among these anthropogenic factors remain underexplored. By analyzing 2356 soil metagenomes from around the world, we developed a comprehensive soil health‐microbial index that integrates microbial diversity, nutrient cycling potential, metabolic potential, primary productivity, and health risks to assess how the soil microbiota respond to anthropogenic factors. Our results indicated that the health‐microbial index was the lowest with severe pesticide contamination. Pesticides, in combination with other anthropogenic and climatic factors, exacerbate the decline in this index. Machine learning predictions suggest that the health‐microbial index in approximately 26% of global farmland could decline between 2015 and 2040, even under sustainable development scenarios. Even with strategies to reduce pesticide usage, we cannot completely halt the decline in the health‐microbial index. Our findings highlight that sustaining soil microbial health on a global scale requires addressing not only pesticide management but also broader anthropogenic impacts.

Rainfall and water level fluctuations dominated the landslide deformation at Baihetan Reservoir, China - Yaru Zhu; Haijun Qiu; Zijing Liu; Bingfeng Ye; Bingzhe Tang; Yijun Li; Ulrich Kamp (Journal of Hydrology, 2024)

Effects of different assembly strategies on gene annotation in activated sludge - Meng Liu; Nuohan Xu; Bingfeng Chen; Zhenyan Zhang; Xinyu Chen; Yuke Zhu; Wenjie Hong; Tingzhang Wang; Qi Zhang; Yangqing Ye; Tao Lu; Haifeng Qian (Environmental Research, 2024)

Ultra-thin layer HTaMoO6 catalyst for the upgrading of carbohydrates into 5-hydroxymethylfurfural - Lei Zhang; Bingfeng Chen; Ti Zhou; Xiaomeng Cheng; Minghua Dong; Ye Liu; Huizhen Liu; Qingling Xu; Buxing Han (Chemical Engineering Journal, 2024)

Creep deformation monitoring of landslides in a reservoir area - Bingfeng Ye; Haijun Qiu; Bingzhe Tang; Ya Liu; Zijing Liu; Xingyuan Jiang; Dongdong Yang; Mohib Ullah; Yaru Zhu; Ulrich Kamp (Journal of Hydrology, 2024)